2010
DOI: 10.1007/s00535-010-0292-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of mosapride citrate in proximal gastric accommodation and gastrointestinal motility in healthy volunteers: a double-blind placebo-controlled ultrasonographic study

Abstract: This study shows that mosapride citrate enhances the meal-induced gastric accommodation reflex and promotes adequate gastroduodenal coordination and motility in healthy volunteers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 40 publications
1
43
1
4
Order By: Relevance
“…Ultrasonography has already been used clinically on humans, and gastric motility has been investigated in patients with functional dyspepsia [17], gastric ulcer [9], and diabetes with metabolic syndrome [26]. In addition, the prokinetic effect of 5HT 4 receptor agonist mosapride citrate was investigated using this ultrasonographic method [16]. In contrast, the significance of canine gastric motility is poorly understood because there have been limits to the use of previous assessment methods in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasonography has already been used clinically on humans, and gastric motility has been investigated in patients with functional dyspepsia [17], gastric ulcer [9], and diabetes with metabolic syndrome [26]. In addition, the prokinetic effect of 5HT 4 receptor agonist mosapride citrate was investigated using this ultrasonographic method [16]. In contrast, the significance of canine gastric motility is poorly understood because there have been limits to the use of previous assessment methods in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonographic evaluation of gastric motility in humans has been applied in clinical settings, and several clinical trials have been performed to estimate the pathogenesis of gastric motility disorders on a large scale [9,16,17,26]. Previous reports have described the ultrasonographic assessment of gastric motility or emptying in dogs [7,19].…”
mentioning
confidence: 99%
“…Several pathophysiological causes of FD have been identified, such as delayed gastric emptying (Gilja et al, 1996;Quartero et al, 1998;Kusunoki et al, 2010;Karamanolis et al, 2006), abnormal antroduodenal motility (Stanghellini et al, 1992;Kusunoki et al, 2000), altered sensitivity to duodenal acid or lipid exposure (Burbera et al, 1995;Samson et al, 1999), visceral hypersensitivity (Mertz et al, 1998;Undeland et al, 1998), and impaired accommodation reflex (Salet et al, 1998;Tack et al, 1998). Among these, an impaired accommodation reflex is the most frequently observed pathophysiological condition in patients with FD.…”
Section: Figmentioning
confidence: 99%
“…However, the reproducibility of the measurements was not adequately evaluated. In this regard, we selected and confirmed some landmarks to ensure that the same portion of the stomach was analyzed throughout all the measurements (Hara et al, 2002;Kusunoki et al, 2010). Therefore, we believe that there is very little possibility of inconsistencies caused by human errors in this method.…”
Section: Figmentioning
confidence: 99%
“…In our previous study, we reported that extracorporeal ultrasonography (US) is a useful modality for the assessment of meal-induced gastric AR, gastric emptying rate (GER), antral contractions, and duodenogastric reflux (DGR) (17)(18)(19)(20)(21)(22). The aim of this study was to determine the clinical effects of Rikkunshito on gastric AR and gastroduodenal motility in FD patients by using US.…”
Section: Introductionmentioning
confidence: 99%